Classroom interaction geography: visualizing space & time in classroom interaction. Issue 5 (1st December 2022) - Shapiro, Ben Rydal; Garner, Brette
Abstract: Methods to transcribe and represent classroom video data are central to studying teaching and learning in classrooms. However, current methods focus on encoding and representing data over time, not space. In this paper, we demonstrate the value of a new methodological approach called interaction geography to transcribe and interactively visualize classroom video data over space and time. We use interaction geography to illustrate classroom participation patterns in two case studies from teacher education research that, until now, have been challenging to see. Findings characterize strengths, limitations, and next steps to expand interaction geography in classroom research and suggest new questions to consider when encoding and representing classroom research data over space and time.